Large shareholder participation behaviors, managers' risk-taking and firm innovation performance: A shareholder activism perspective. Issue 1 (5th March 2018) - Zhang, Feng; Yang, Jianjun; Xu, Zhi; Zhu, Guilong
Abstract : Purpose: Focusing on internal corporate governance, the purpose of this paper is to apply the shareholder activism perspective to consider how large shareholder participation behaviors might influence firm innovation performance. Specifically, "confrontationally strategic intervention" and "cooperatively strategic consensus" participation behaviors are examined and hypothesized to have different effects on managers' risk-taking and firm innovation performance. Design/methodology/approach: Drawing on 182 Chinese firm samples, this paper applies hierarchical ordinary least-squares regression analysis to test the proposed hypotheses. Findings: The results show that strategic intervention was negatively associated with managers' risk-taking and firm innovation performance, while strategic consensus positively affected managers' risk-taking and firm innovation performance. Moreover, managers' risk-taking fully mediated the influence of strategic intervention on firm innovation performance, whereas it partially mediated the influence of strategic consensus on firm innovation performance. Originality/value: The study extends research on shareholder participation by construing that large shareholders' participation behaviors can significantly influence managers' risk-taking and corporate innovation performance, further deepening the understanding of the influences of large shareholders on the firm-level outcomes. The theoretical and practical implications of this finding are also discussed.